Heracleum persicum: chemical composition, biological activities and potential uses in poultry nutrition. Issue 2 (29th April 2019) - CHANGXING, L.; DONGFANG, D.; LIXUE, Z.; SAEED, M.; ALAGAWANY, M.; FARAG, M.R.; CHENLING, M.; JIANHUA, L.
Abstract : Heracleum persicum (golpar) is an endemic medicinal plant that is commonly known as hogweed or Persian hogweed. It contains flavonoids and furanocoumarins that probably could stimulate both cell- and antibody-mediated immune responses. Besides, golpar has a substantial immunostimulatory effect on beta-lymphocytes and macrophages that played important role in antibody synthesis. Its extract at a supplementation level of 1-2.5 ml/l in drinking water showed a remarkable increase in the total immunoglobulins (Ig) (70%), immunoglobulin G (IgG) (100%) and immunoglobulin M (IgM) (94%) titres and an increase in antibody titre against Newcastle disease virus (96%) in broilers. In addition, supplementation positively affected the feed intake (9.4%), weight gain (14.7%) and food conversion ratio (FCR) (8.7%) in broilers. Moreover, in several studies, it has potential as an antifungal, antidiabetic, hypocholesterolaemic and growth enhancer agent; which endorsed its extensive contents of phytochemicals (terpenoids, triterpenes, furanocoumarins, volatile substances, flavonoids and alkaloids). It has a positive effect on the levels of glutathione (GSH), peroxidation lipids (MDA), the total antioxidant capacity of plasma or ferric reducing ability of plasma (FRAP) and glutathione s-transferase (GST), in addition to modulatory effects on liver enzymes including alanine transferase (ALT) and aspartate transferase (AST). After reviewing the published literature, it was apparent that golpar has multidimensional biological effects. Nevertheless, little research is available on the effects of golpar on productive performance and other health-related parameters in avian species. Hence, this review encourages veterinarians and poultry researcher to undertake further work to demonstrate the promising beneficial effects of golpar at effective levels to potentially replace the synthetic antibiotic growth promoters in commercial poultry diets.